Species delimitation by DNA barcoding reveals undescribed diversity in Stelliferinae (Sciaenidae) - Fernanda da Silva, Tárcia (2023)
Stelliferinae is the third most speciose subfamily of Sciaenidae, with 51 recognized species arranged in five genera. Phylogenies derived from both morphological and molecular data support the monophyly of this subfamily, although there is no general consensus on the intergeneric relationships or the species diversity of this group. We used the barcoding region of the cytochrome oxidase C subunit I (COI) gene to verify the delimitation of Stelliferinae species based on the Automatic Barcode Gap Discovery (ABGD), Generalized Mixed Yule Coalescence (GMYC), and Bayesian Poisson Tree Process (bPTP) methods. In general, the results of these different approaches were congruent, delimiting 30–32 molecular operational taxonomic units (MOTUs), most of which coincided with valid species. Specimens of Stellifer menezesi and Stellifer gomezi were attributed to a single species, which disagrees with the most recent review of this genus. The evidence also indicated that Odontoscion xanthops and Corvula macrops belong to a single MOTU. In contrast, evidence also indicates presence of distinct lineages in both Odontoscion dentex and Bairdiella chrysoura. Such results are compatible with the existence of cryptic species, which is supported by the genetic divergence and haplotype genealogy. Therefore, the results of the present study indicate the existence of undescribed diversity in the Stelliferinae, which reinforces the need for an ample taxonomic review of the fish in this subfamily